A non-linear rainfall-runoff model applied to Amazon small catchments with limited data to simulate the flow duration curves. (1st January 2011) - Quintas, Marlus Chaves; Blanco, Claudio J.C.; Amarante Mesquita, André L.
In Amazon, hydroelectric power production excludes ungauged small catchments. Thus, the main objective of this paper is the implementation of a non-linear rainfall-runoff model on small catchments in the Amazon region to simulate flow duration curves for the hydropower production. Because the rainfall-runoff process is non-linear, modification is applied to a simple linear model based on the residuals relationship between the simulated and observed discharges. For calibration and sensitivity analysis of the model, seven years to one year of rainfall and flow data were used; and for validation, seven-year data from a small source catchment were used. The sensitivity analysis determined that the minimum length of data is 18 months. Thus, the model was applied in an experimental catchment with 1.5 year of data. The good results of the model application showed that it could be applied in other small catchments with limited data in the Amazon region to simulate flow duration curves.